Changes in obese metabolic phenotypes over time and risk of incident chronic kidney disease. Issue 12 (30th July 2018) - Nam, Ki Heon; Yun, Hae‐Ryong; Joo, Young Su; Kim, Joohwan; Lee, Sangmi; Lee, Changhyun; Park, Kyoung Sook; Park, Jung Tak; Chang, Tae‐Ik; Kang, Ea Wha; Yoo, Tae‐Hyun; Kang, Shin‐Wook; et al.
Abstract : Aim: To examine the association between metabolically healthy obese (MHO) phenotype and incident chronic kidney disease (CKD) and study whether changes in metabolic phenotypes over time could affect CKD risk. Methods: A total of 8589 subjects from the Korean Genome and Epidemiology Study were categorized into four groups based on the presence of obesity and metabolic abnormalities (MA). The primary endpoint was an onset of incident CKD defined as an estimated glomerular filtration rate of ≤ 60 mL/min/1.73 m 2 . Multivariable Cox analysis and time‐varying Cox analysis were performed to delineate the relationship between obese metabolic phenotypes and incident CKD after adjustment for sociodemographic factors and clinical and laboratory parameters. Results: During a mean follow‐up duration of 9.3 years, CKD occurred in 782 (9.1%) participants. In the multivariable Cox model, the hazard ratio (HR) for incident CKD in the MHO, metabolically abnormal non‐obese (MANO), and metabolically abnormal obese (MAO) groups was 1.42 ( P = 0.002), 1.45 ( P < 0.001), and 1.77 ( P < 0.001), respectively, compared with the metabolically healthy non‐obese (MHNO) group. Time‐varying analysis with these four phenotypes as time‐varying exposures showed the same results. Furthermore, subjects with persistent MHO through follow‐up were at a 2.0‐fold increased risk of CKD ( P < 0.001). 41.0% of subjects experienced phenotype changes during follow‐up. Over the long term, the MHO group had a higher proportion of transition to the MA phenotype and unfavourable metabolic profiles than the MHNO group. Among MHO subjects, those who transitioned to MAO were at a 4.1‐fold increased risk of incident CKD than those who regressed to MHNO. In addition, transition to MHO from other groups carried a higher risk of CKD than persistent MHNO. Conclusion: MHO subjects are at increased risk for incident CKD.